AKTUALISASI PENDIDIKAN ISLAM PADA MASA NABI MUHAMMAD SAW DENGAN PENDIDIKAN ISLAM PADA MASA MODERN - Putri, Oktia Anisa (INCARE, International Journal of Educational Resources, 2023)
The purpose of this study is to describe how the actualization of Islamic education during the time of the Prophet Muhammad SAW with Islamic education in modern times. To express this, researchers use library research methods with types of historical analysis research and data collection techniques taken from various literature that discusses the theme in question. The data that has been collected is then analyzed using content analysis techniques. The results of the study revealed that of the various methods implemented by the Holy Prophetsa in implementing Islamic Education and actualized in modern times, the most interested students are the Uswah method (Suri a good example), although basically all of the methods offered have their own advantages and the goals must be good. The main focus when in Makkah is to instill Tawhid Education, in changing the character of students, it is preferred to change their beliefs first because the change for the better is only by cleaning first through the path of Tawhid. Given the early background of the condition of the society is idolatrous, hobbies of killing girls, gambling and so on. After in Medina, the cultivation of the value of education has begun to show real results because there have been many followers of high loyalty without worrying about consistency.